The incidence of tuberculosis in the indigenous population and its determining factors: An integrative literature review (Research, Society and Development, 2021)
The present study aims to identify the factors behind the occurrence of tuberculosis in the indigenous population; map this disease between 2015 to 2019, in the northern region of Brazil, and contribute to addressing this problem. A descriptive study was carried out, of the type integrative literature review (RIL), focusing on specialized articles, review of evidence on the determining factors for the emergence and prevalence of tuberculosis in indigenous populations. Nine articles published in journals between 2016 and 2021 were selected in the following bibliographic databases: Biblioteca Virtual em Saúde (BVS) and PubMed. Thus, 6 articles (66.7%) were found in the VHL database and 3 (33.3%) in PubMed. Most of the studies deal with determining factors for discontinuing treatment, socioeconomic issues, difficult accessibility - such as health units and diagnostic inaccuracy. In addition, there are reports of exclusion, invisibility and discrimination. All of this puts indigenous communities in situations of vulnerability. Overcoming the factors that make tuberculosis prevalence feasible in these categories involves multisectoral issues: public policies, income distribution, accessibility to health systems and the implementation of the PNCT are some of the essential points for reducing cases.